2013
DOI: 10.1364/josaa.30.001394
|View full text |Cite
|
Sign up to set email alerts
|

Statistical quantification of the effects of viewing distance on texture perception

Abstract: In general, viewers are more attracted to local features in images at a shorter viewing distance and to global features in images at a longer viewing distance. However, numerical analysis of the effect of viewing distance on human texture perception and how the perception of global and local changes under certain conditions are still undetermined. In this paper, we present statistical prediction of the relationship between the domination ratio of global and local features and the viewing distances under the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The potential of texture analysis has been demonstrated in numerous biomedical applications, including OCT imaging of skin [7], bladder [8], eye [9], atherosclerotic plaque [10], esophagus [11], and breast [12]. In general, texture analysis techniques can be classified into three groups: statistical technologies [310], spectral technologies [11, 12], and structural technologies [13]. The choice of optimal method for texture analysis may vary depending on the specific biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of texture analysis has been demonstrated in numerous biomedical applications, including OCT imaging of skin [7], bladder [8], eye [9], atherosclerotic plaque [10], esophagus [11], and breast [12]. In general, texture analysis techniques can be classified into three groups: statistical technologies [310], spectral technologies [11, 12], and structural technologies [13]. The choice of optimal method for texture analysis may vary depending on the specific biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Dulaney and Marks [16] reported that global interference decreases with training, whereas local interference develops with training. Li et al [17] noted that prior knowledge and viewing distance also affect global precedence in humans in tasks involving similarity selection.…”
Section: Introductionmentioning
confidence: 99%
“…Viewers are attracted to local features when viewing images from a short distance and to global features when viewing images from a long distance. In [17], a logistic-regression model was built to construct a statistical relationship between viewing distance and visual perception of global/local features. In this research, viewing distances in the visual-similarity experiment were determined according to the distance equation proposed in [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we constructed a VR system and applied it to investigate the visual complexity perceptions of texture images in 2D and 3D conditions. One of the reasons we chose textures as the stimuli in this study is that the properties of textures are more accessible and easier to manipulate than natural images [35]. Moreover, the visual perception of textures can be represented in a lower feature space.…”
Section: Introductionmentioning
confidence: 99%